Real Time Monitoring of Diesel Engine Injector Waveforms for Accurate Fuel Metering and Control - Q. R. Farooqi; B. Snyder; S. Anwar (Journal of Control Science and Engineering)
This paper presents the development, experimentation, and validation of a reliable and robust system to monitor the injector pulse generated by an engine control module (ECM) which can easily be calibrated for different engine platforms and then feedback the corresponding fueling quantity to the real-time computer in a closed-loop controller in the loop (CIL) bench in order to achieve optimal fueling. This research utilizes field programmable gate arrays (FPGA) and direct memory access (DMA) transfer capability to achieve high speed data acquisition and delivery. This work is conducted in two stages: the first stage is to study the variability involved in the injected fueling quantity from pulse to pulse, from injector to injector, between real injector stators and inductor load cells, and over different operating conditions. Different thresholds have been used to find out the best start of injection (SOI) threshold and the end of injection (EOI) threshold that capture the injector “on-time” with best reliability and accuracy. Second stage involves development of a system that interprets the injector pulse into fueling quantity. The system can easily be calibrated for various platforms. Finally, the use of resulting correction table has been observed to capture the fueling quantity with highest accuracy.